PENGEMBANGAN SISTEM REGISTRASI PASIEN RAWAT INAP DI RUMAH SAKIT UMUM DAERAH KOTA PADANGSIDIMPUAN - arifah masyitah; Ria Masniari; Yusniwarti Yusad (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2013)
ABSTRACT Hospital Information System is an important component in making efforts to improve the quality of health services at the hospital. In Padangsidimpuan General Hospital patient records was done manually, so that it was still encountered weakness, especially in in-patients registration. Therefore, to handle it is needed the development of in-patients registration system by using computer technology. The aim of in-patients registration system development in Padangsidimpuan General Hospital are to facilitate and improve the accuracy of in-patients registration in this hospital. The development of this system used System Development Life Cycle (SDLC) method. Stages of this process were planning, analysis, design, and implementation has been done only on trial, meanwhile use phase was not made. Results of in-patients registration system development consists of three sub-systems, namely input sub system (patient’s identity data, doctor’s identity data, medical record officer data, room’s data, and diagnosis data), process sub system (data processing program), and output sub system (report of admission patients per day, report of discharge patients per day, report of patients per month, report of patients per year, and report of number of diseases per year). In-patients registration system makes in-patients registration of hospital easier and informing about physician, availability of ward, and room where patient’s treated. Hopefully, Padangsidimpuan General Hospital disposed to use and prepares facilities and infrastructures to support this system.